Carbon dioxide fixation method for electrosynthesis of benzoic acid from chlorobenzene - Abdul Jalil, Aishah; M. A., Hartini; S., Normala; A. M., Norhuda; M. H., N. Hanis; H. M., Razif; T., Sugeng (Chengdu Institute of Organic Chemistry, 2007)
Carbon dioxide fixation technique was developed as an alternative dechlorination method of chlorobenzenes. Electrolysis of chlorobenzene was carried out in a one-compartment cell fitted with an aluminium anode and a platinum cathode. Electrolysis in N, N-dimethylformamide (DMF) solution containing 0.1 M of tetrapropylammonium bromide (TPAB) at 0 Â°C, 100 ml/min of CO2 flow rate and 120 mA/cm2 of current density was found to be the optimum conditions of this electrocarboxylation, which gave 72% yield of benzoic acid from chlorobenzene. These conditions were then applied to 1,2-dichlorobenzene and 1,3-dichlorobenzene in order to convert them to their corresponding benzoic acids.